Zastosowanie analizy dyskryminacyjnej do badania stałości wariancji składników losowych w jednorównaniowych modelach ekonometrycznych - Grześkowiak, Alicja (Using of the Discriminant Analysis in the Process of Evaluating the Stability of the Variance of Disturbances in the Single-Equation Econometric Models, 2007)
The paper presents the application of the discriminant analysis to the evaluation of chosen assumptions of the econometric model is presented. The approximation of the inverse matrix by the Neumann's series is proposed. The empirical examination referring to the security characteristic lines was carried out applying the proposed method. The results were compared with the results obtained from classic approach - hypotheses testing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (18); 2007; nr 1151, s. 38-49